Interpretation Of Spiritual And Ethical Values In The Works Of Sufi Olloyor (Open Academia: Journal of Scholarly Research, 2025)
This article examines the interpretation of spiritual and ethical values in the works of Sufi Olloyor, one of the prominent representatives of Central Asian Sufi thought. The study analyzes how the poet integrates the principles of sharia, tariqa, ma‘rifa, and haqiqa into his writings, presenting them in a form accessible to the broader public. Special attention is given to his approach to moral education, the cultivation of the complete human being, and the reinforcement of Islamic spiritual heritage during a period of social and political instability. By exploring key texts such as Sabot ul-ojizin, the article reveals Sufi Olloyor’s efforts to restore authentic Sufi teachings, counteract pseudo-mysticism, and shape the moral consciousness of society. The findings highlight the significance of his intellectual legacy for understanding the moral-philosophical foundations of Sufism in the region